Columbus Sustainable Energy Converter - et al., K C Charan (International Journal of Advanced Science and Technology, 2019)
Now-a- days “Energy Conservation” is the word on which the world is focusing its vision. Electric energy has become the most prominent source of energy for driving any device. Most of the mechanical devices run with the help of electrical energy. The production of electric energy is expensive. In developing countries like India, electric power is generated economically from thermal power plants. The methods of producing electric power in these countries is enormously polluting the atmosphere leading to adverse problems like global warming, green house effects etc., So, reducing the use of electric power wherever possible can reduce our dependency on electric power there by reducing air pollution. Conservation and reutilization of energy can be done by effective usage of sustainable energy sources. Finding suitable energy sources and extracting specific work output from them plays a prominent role in energy conservation.